ANALISIS PRODUKTIVITAS KOMBINASI ALAT BERAT PADA PEKERJAAN GALIAN TEBING PROYEK PEMBANGUNAN JJLS TEPUS – JERUKWUDEL GUNUNGKIDUL - Bima Aditya; Cahyo Dita Saputro (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2023)
Heavy equipment is a very important supporting factor in a project work, especially on a large scale of work. The use of heavy equipment aims to facilitate human resources in carrying out the work. Especially in the Gunungkidul district, currently there are a lot of construction of the Southern Cross Road (JJLS). Because Gunungkidul has a geographical location of limestone or karst mountains, it is not possible if this development is carried out using only human resources. Therefore, this study focuses on the productivity of the heavy equipment group which includes excavator breaker, excavator bucket, and dump truck by applying the MPDM (Method Productivity Delay Model) method. In this study, it can be seen the productivity of each working heavy equipment, production cycle delays and equipment operational costs. Based on the calculation results, the average productivity value of excavator breaker is 5.97 m3/hour, excavator bucket is 67.49 m3/hour, and dump truck is 8.03 m3/hour. Then the calculation of the cycle time that is not delayed on the dump truck only counts on day 1 and day 3 because on other days the dump truck does not experience a time delay, then the calculation results obtained on day 1 are 4.69 minutes and on day 1. 3 by 32.86 minutes.Keywords: Excavator Breaker, Excavator Bucket, Dump Truck, Technic MPDM